Clinical and histologic evaluations of healing in an extraction socket filled with platelet-rich fibrin - Jiing-Huei Zhao; Chung-Hung Tsai; Yu-Chao Chang (Elsevier, 2011)
Platelet-rich fibrin (PRF) is an immune and platelet concentrate that contains all constituents of a blood sample favorable to healing and immunity on a single fibrin membrane. However, limited information is currently available concerning the histologic healing of extraction sockets using PRF. This report presents the clinical and histologic characteristics of a patient who underwent a tooth extraction which was filled with PRF. The right mandibular second molar was removed from a 47-year-old male patient, and the socket was filled with PRF as the sole grafting material in preparation for placing an implant after wound healing. The extraction site was reentered surgically for implant placement. A cylindrical sample core of the newly formed tissue was collected from the socket for histological evaluation. During clinical healing, neither infectious episodes nor untoward clinical symptoms were seen. At the time of implant insertion, the socket was completely filled by a hard material, which on probing exhibited the consistency of bone. A histological exanimation of the core taken from the socket revealed new bone formation. There was also no evidence of inflammatory infiltrates. The clinical and histological findings suggest that filling a fresh extraction socket with PRF provides a viable therapeutic alternative for implant site preparation.